Myth and reality about civil servants’ duty of obedience and the distinction between illegal and clearly illegal decisions - Fenger, Niels; Gram, Mette Kryger (Politica, 2016)
In recent years’ debate on the interaction between ministers and civil servants, it has been argued that the obligation of civil servants to keep within the law is in fact hollow, since the current rules allow the government to get away with just about anything, as long as the actions are not clearly illegal. This article seeks to explain why Danish law distinguishes between illegal and clearly illegal orders, and when this distinction is relevant. It is the authors’ opinion that the criterion of clarity does not undermine the principle of a legally bound public administration that has a duty to speak the truth and act in accordance with the law.